Disseminação informacional em bibliotecas universitárias: uma vertente expressa por uma carta de serviços - Paulo Fernando da Silva (2019)
Basic guidelines of Decree No. 6.932 of 2009, known as "citizen decree" and other developments established procedures and quality standards for the preparation and disclosure of a document entitled "service letter". It is a written text, public management and informational, adopted by several countries and whose purpose is to promote simplification of service to the public through the dissemination of information to society. The obligation to comply with this rule falls, in the Brazilian case, on the organs and entities of the federal executive branch that provide services to citizens, such as university libraries. Among the forms chosen by the legislation to promote the disclosure of service letters are the institutional portals of universities hosted on the Internet. In this sense, this exploratory and documentary research sought to identify the presence of norms standardized by the decree in the excerpts of service letters that project information on the activities of public attendance of university libraries. In addition, it also analyzed the websites of these agencies in search of complementary information of the same nature and level. It was intended, therefore, to answer the main guiding question of this research, that is to say, "Since the information contained in the letters of services published by the universities were configured according to the provisions of the citizen decree in the part containing specific information on university libraries?" And, thus, contribute to the improvement of public service regarding the availability of information for users of university libraries under the prism of the values of public transparency. The methodology was based on a qualitative study of the service letters published by 62 Federal Institutions of Higher Education in the country, as well as on the evaluation of the information contained in the websites of the libraries of all these selected institutions. For the definition of the sample, the university evaluation criteria produced by the Brazilian Ministry of Education and measured by the General Index of Courses were used. As a complement, documentary research was also carried out, mainly, on the legislation concerned. The results have shown that, with regard to the part of service letters dealing with libraries, the information disclosed is not compatible with the guidelines established by the relevant regulatory bodies. It was also found that some of the information that was not included in these documents was available on the websites. Therefore, it becomes evident the need to promote adaptations and improvements in this section of the service charters, in order to meet, with greater ownership, the provisions of the citizen decree.